2018
DOI: 10.14218/jcth.2018.00046
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Viral Induction of Biliary Atresia: A Review

Abstract: Biliary atresia (BA) is a childhood disease which manifests with abnormal narrowing, blockage or complete absence of bile ducts within the liver. Many possible etiologies have been reported for the development of BA, including congenital, perinatal and acquired conditions. Since the 1970’s, there has been increasing evidence linking BA development to viral perinatal infections. The viral vectors most commonly implicated include members of the herpesviridae family (cytomegalovirus and Epstein-Barr virus) as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 87 publications
(118 reference statements)
0
46
0
Order By: Relevance
“…Biliary atresia is a progressive bile duct disorder in infants representing cholestasis, jaundice, and liver fibrosis (29). Although previous studies has suggested the association between perinatal viral infection and biliary atresia development in infants, detailed mechanisms of pathogenesis in biliary atresia are still undefined (30). Chen et al have performed genomewide association study using a cohort of 343 non-related biliary atresia patients and 1,716 healthy controls to identify susceptible loci to biliary atresia (31).…”
Section: Biliary Atresiamentioning
confidence: 99%
“…Biliary atresia is a progressive bile duct disorder in infants representing cholestasis, jaundice, and liver fibrosis (29). Although previous studies has suggested the association between perinatal viral infection and biliary atresia development in infants, detailed mechanisms of pathogenesis in biliary atresia are still undefined (30). Chen et al have performed genomewide association study using a cohort of 343 non-related biliary atresia patients and 1,716 healthy controls to identify susceptible loci to biliary atresia (31).…”
Section: Biliary Atresiamentioning
confidence: 99%
“…Biliary atresia (BA) occurs in one out of every 10,000-15,000 live births, and causes bile duct inflammation because of the blockage of bile flow during the perinatal period (Hartley et al, 2009;Mieli-Vergani and Vergani, 2009). Bile duct injury in extrahepatic bile ducts (EHBDs) may occur in the early pathogenesis of BA (Bezerra et al, 2018), possibly through viral infection (Averbukh and Wu, 2018), toxin exposure (Lorent et al, 2015) and/or individual genetic/epigenetic predisposition (Girard and Panasyuk, 2019) during fetal and perinatal periods (Mack and Sokol, 2005;Nakamura and Tanoue, 2013;Davenport, 2016). BA is traditionally classified into two forms: an 'embryonic' form in a minority (30%) of cases and a 'perinatal' form in the majority (70%) of patients (Balistreri et al, 1996;Bezerra, 2005;Makin and Davenport, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, only the rotavirus ‐ induced murine BA is close to human BA, because it brings together the immune responses found in the human disease. Studies on human BA livers have reported contradictory results, with rotavirus rates ranging from 0% to 15% for rotavirus A and up to 40% for rotavirus C. One animal model showed that the rotavirus was no longer detectable shortly after having induced BA‐like disease, but its role can be witnessed by high serum titres of rotavirus immunoglobulin M and immunoglobulin G . However, the seroprevalence of group A immunoglobulin M in BA infants in one study did not differ from that of non‐BA matched‐age cholestatic controls .…”
mentioning
confidence: 96%
“…Although the authors add to our knowledge about the link between the rotavirus vaccination and BA, their study had limitations, like most on this topic. The main inevitable limitation was the poor generalisability of the results as they only studied Korean subjects in the context of the still uncertain issue of BA seasonality in Korea . In addition to the unfortunate lack of information on which rotavirus group was associated with BA in their study, there were no details on feeding mode.…”
mentioning
confidence: 99%
See 1 more Smart Citation